Mother-and-child zinc - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Mothers-to-be should be encouraged to eat zinc-enriched rice according to a report published in June 2001 after a workshop of the University in Wageningen, the Netherlands. Including zinc in pregnant women s diets improves the resistance of the...